The Developing of Performance Assessment to Calculate Scope and Volume of Cube and Block Competence in The Mathematic Learning of Junior High School - Ulfa, Khofina; Kartono, Kartono; Khumaedi, Muhammad (Universitas Negeri Semarang, 2018)
Assessment of performance tests is part of the implementation curriculum of 2013 that can not be implemented by many teachers because there are obstacles such as the absence of standard instruments so that teachers feel difficulty.This research is a study to develop performance assessment test on mathematics learning to calculate scope and volume of cube and block for junior high school in 2013 curriculum that is valid, reliable, practical. Method of this research used research development with adapted from Djemari Mardapi (2016 : 132) to 9 – steps of development. The validity of the instrument contents is tested by 3 experts in the field, the score given by the expert is tested using V Index, and reliability with interarter using the coefficient of Ebel procedure. Data Analisys on field used construct validity with Exploratory Factor Analysis (EFA) and reliability used alpha cronbach. The result showed that instrument of validation test from 10 object assessment test performance through expert judgment produced coefficient of validation that has score of coefficient > 0,3 and reliability of 0,88. Data analysis on field test from could see on KMO that showed score of KMO 0,689 that has meaning was the number of instrument test analyzed more deep. The analysis performance test assessment produced 3 factore are product, process, and accommodates task. The result used reliability test of Alpha Cronbach also got coefficient 0,706. Test of practicality, from 3 mathematics teacher respondents stated practical with score 46,67 which means practical use. This research is expected to develop standardized tests to measure the assessment of performance tests on mathematics learning of junior high school to calculate scope and volume of cubes and block.